2020
DOI: 10.1021/acs.jproteome.0c00151
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Derived Extracellular Vesicle Phosphoproteomics through Chemical Affinity Purification

Abstract: Invasive nature and pain caused to patients inhibit the routine use of tissue biopsy-based procedures for cancer diagnosis and surveillance. The analysis of extracellular vesicles (EVs) from biofluids have recently gained significant traction in the liquid biopsy field. EVs offer an essential "snapshot" of their precursor cells in real time and contain information-rich collection of nucleic acids, proteins, lipids, etc.The analysis of protein phosphorylation, as a direct marker of cellular signaling and diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 70 publications
(140 reference statements)
1
77
0
Order By: Relevance
“…EVs enriched by EVtrap met required EV physical characteristics according to the MISEV 2018 criteria [ 2 ]. Size distribution measured was lower than 200 nm, underlying that EVtrap beads capture a small EV subset, as demonstrated in previous studies [ 25 , 26 ]. EVs were also shown by western blot to contain common well-characterized markers-PDCD6IP and TSG101 [ 28 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…EVs enriched by EVtrap met required EV physical characteristics according to the MISEV 2018 criteria [ 2 ]. Size distribution measured was lower than 200 nm, underlying that EVtrap beads capture a small EV subset, as demonstrated in previous studies [ 25 , 26 ]. EVs were also shown by western blot to contain common well-characterized markers-PDCD6IP and TSG101 [ 28 ].…”
Section: Discussionsupporting
confidence: 73%
“…EVs from primary human brain microvascular endothelial cells were isolated using an EVtrap isolation method based on a chemical affinity capture approach, permitting to isolate small extracellular vesicles [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most immunocapture assays use monoclonal antibodies immobilized on a solid-phase (e.g., magnetic beads) to capture EVs that expose a specific ligand [ 57 , 58 , 59 , 60 ]. Other affinity isolation methods use chemical affinity [ 61 , 62 ] or annexin A5 which binds to phosphatidylserine moieties on the surface of most EVs [ 63 ]. Based on specific ligands or proteins, immunocapture can isolate subpopulations of EVs [ 21 , 64 ].…”
Section: Exosome Isolation and Characterizationmentioning
confidence: 99%
“…With ExoQuick or UC, ~300 [ 92 ] and ~100 proteins [ 86 ] were identified with ~32% and ~70% annotated as exosomal proteins, respectively. The highest number of exosomal proteins in plasma/serum reported so far was 2238 using immunoaffinity isolation with only 5 µL of plasma [ 61 ]; however, the GO term analysis showed that only 18.4% were annotated as exosomal proteins, suggesting issues with exosomal purity.…”
Section: Exosomal Proteins As Biomarkers For Pca and Bcamentioning
confidence: 99%
“…Careful consideration of the EVs isolation method must be taken into account when interpreting study results. The most common methods are a series of differential centrifugation steps, ultrafiltration, chemical affinity purification, and Exoquick [39][40][41] (Table 1). As demonstrated in conditional medium from cell culture the purification methods of EVs may heavily influence the yield, purity, and integrity of RNA extracted from EVs [42,43].…”
Section: Profiling Evs-mirnasmentioning
confidence: 99%